Enabling remote assessment of cognitive behaviour through mobile experience sampling - Wohlfahrt-Laymann, Jan; Hermens, Hermie; Villalonga, Claudia; Vollenbroek-Hutten, Miriam; Banos, Oresti (2018 IEEE International Conference on Pervasive Computing and Communications Workshops, PerCom Workshops 2018, 2020)
Cognitive decline is among the normal processes of ageing, involving problems with memory, language, thinking and judgment, happening at different times and affecting people's live to a significant extent. Traditional clinical methods for cognitive assessment are conducted by experts once first symptoms appear. Mobile technologies can help supporting more immediate, continuous and ubiquitous measurements, thus potentially allowing for much earlier diagnosis of cognitive disorders. We present in this paper a digital mobile tool to administer cognitive tests in the form of multimedia experience sampling methods (ESM), which can run on a smartphone and can be scheduled and assessed remotely. The tool integrates digital cognitive ESM with passive sensor data that can be used to study the interplay of cognition and physical, social and emotional behaviours. We implement the Mini-Mental State Examination (MMSE) test, a clinical questionnaire extensively used to assess cognitive disorders, in order to showcase the possibilities offered by the proposed tool. Initial usability results show the tool to be perceived simple, easy and accessible for cognitively unimpaired persons.
Ponencia de la conferencia "2018 IEEE International Conference on Pervasive Computing and Communications Workshops, PerCom Workshops 2018; Athens; Greece; 19 March 2018 through 23 March 2018"
Keywords: cognitive assessment; human behaviour; mHealth; mobile sensing; smartphone; Scopus(2); WOS(2)